1992
DOI: 10.1093/ajcn/55.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daytime protein restriction on nutrient intakes of free-living Parkinson's disease patients

Abstract: Studies have shown that severe daytime restriction of dietary protein improves the efficacy of L-dopa and reduces response fluctuations in some Parkinson's disease (PD) patients. This study investigated the nutritional adequacy of the daytime restricted-protein diet. Eleven free-living PD patients suffering from unpredictable response fluctuations to L-dopa were counseled to limit protein intake to approximately 10 g before 1700. Three sets of 6-d food records obtained during the 8-wk study showed that while o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…As in other studies with PD (7,19), our sample showed no risk of malnutrition by BMI classification. However, these patients (table 1) have a lower BMI compared with healthy elderly subjects from the same region of the country (BMI = 28.9 kg /m²) (20).Therefore, the BMI elderly rates have limitations and may not be used exclusively, since this indicator assesses only the body mass without defining its distribution (21).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As in other studies with PD (7,19), our sample showed no risk of malnutrition by BMI classification. However, these patients (table 1) have a lower BMI compared with healthy elderly subjects from the same region of the country (BMI = 28.9 kg /m²) (20).Therefore, the BMI elderly rates have limitations and may not be used exclusively, since this indicator assesses only the body mass without defining its distribution (21).…”
Section: Discussionsupporting
confidence: 86%
“…In most cases, the progression of Parkinson's disease is accompanied with consequent loss of weight (1,7,11,18,19). The weight loss is continuous and may begin before the disease diagnosis (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An average of 21Kcal/kg of body weight per day was registered, showing that the assessed individuals consumed a reduced calorie diet. In the study by Pare et al, 31 the individuals presented an average intake of 2163 Kcal, with an average of 39 Kcal/Kg body weight per day, characterizing a high calorie diet intake. The prescription of a norm-, hypo-or hyper-calorie diet for patients with PD will depend on their nutritional status.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Fracasso et al, 9 higher protein intake during the day was also observed, with consumption between breakfast and the afternoon snack representing 70.4% of the total daily protein intake. In the study by Pare et al, 31 it was observed that, by prioritizing the majority of protein content in the diet at night, there is a reduction of the motor fluctuations that may be caused by the interaction of the protein with levodopa. Ideally protein intake should be higher at night than during the day.…”
Section: 34mentioning
confidence: 99%